Understanding The Important Role of Online Customer Reviews in Social Commerce on Customer Trust and Impulse Buying - Sanapang, Gracela Marisa; Ardyan, Elia; Christian, Sonata (International Business Management - Universitas Ciputra, 2024)
This research aims to investigate the impact of online customer reviews on customer trust and impulse buying, by utilizing the Stimulus-Organism-Response (SOR) theoretical framework. Furthermore, it examines the impact of customer trust as a mediating variable between online customer reviews and impulse buying. Data was obtained through the use of an online questionnaire which was filled out satisfactorily by a total of 150 participants. Participants in this research were individuals who had engaged in impulsive online purchasing behavior and demonstrated consumer trust. The method used in this research involves utilizing Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings show that online customer reviews significantly influence consumer trust and impulse buying, while consumer trust significantly influences impulse buying. Moreover, consumer trust partially mediated the relationship between online customer reviews and impulse buying. This research encourages online customer reviews for social commerce in Indonesia. When customer trust increases, consumers will make impulse purchases based on recommendations. Individuals who show a tendency to engage in impulsive online purchasing behavior are supported by the trust that the individual has. This research provides theoretical and practical implications that can provide valuable insight for further online consumer purchase research.